2008
DOI: 10.1146/annurev.physchem.59.032607.093749
|View full text |Cite
|
Sign up to set email alerts
|

Ions at Aqueous Interfaces: From Water Surface to Hydrated Proteins

Abstract: The surfaces of aqueous solutions are traditionally viewed as devoid of inorganic ions. Molecular simulations and surface-selective spectroscopic techniques show, however, that large polarizable anions and hydronium cations can be found (and even enhanced) at the surface and are involved in chemistry at the air/water interface. Here, we review recent studies of ions at the air/water interface and compare from this perspective water with other polar solvents. For water, we focus in particular on the surface beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
287
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(304 citation statements)
references
References 154 publications
(238 reference statements)
14
287
1
2
Order By: Relevance
“…Since sodium ions contain fewer electrons than chloride ions, our SAXS results suggest that water molecules are ''contracting'' locally more around acidic than around basic surface residues and that protein HS properties are a combined result of a residue-specific ionic interaction and structural changes of water molecules in their vicinity. Indeed, an important factor not taken into account by most SAXS/ SANS programs is the contribution of solvent ions in the vicinity of proteins, which may display concentrations that vary significantly from those in the bulk as a function of the local physicochemical protein surface properties (24,25). Recent MD simulations suggest that ions may either bind specifically and locally to oppositely charged protein surface residues (67,68) or accumulate at nonpolar surface patches (66) as a function of type (i.e., anions/cations) and size, an observation supported by SANS experiments with varying salt concentrations and type (5,33).…”
Section: Protein Hs Density and Ionic Composition Depend On The Surfamentioning
confidence: 99%
See 1 more Smart Citation
“…Since sodium ions contain fewer electrons than chloride ions, our SAXS results suggest that water molecules are ''contracting'' locally more around acidic than around basic surface residues and that protein HS properties are a combined result of a residue-specific ionic interaction and structural changes of water molecules in their vicinity. Indeed, an important factor not taken into account by most SAXS/ SANS programs is the contribution of solvent ions in the vicinity of proteins, which may display concentrations that vary significantly from those in the bulk as a function of the local physicochemical protein surface properties (24,25). Recent MD simulations suggest that ions may either bind specifically and locally to oppositely charged protein surface residues (67,68) or accumulate at nonpolar surface patches (66) as a function of type (i.e., anions/cations) and size, an observation supported by SANS experiments with varying salt concentrations and type (5,33).…”
Section: Protein Hs Density and Ionic Composition Depend On The Surfamentioning
confidence: 99%
“…Increased water density in the first hydration shell (HS), as well as surface-specific differences in the organization of the hydration water, have been reported by MD simulations (17)(18)(19)(20) and have been described thermodynamically in terms of electrorestriction (21). MD studies involving nucleic acids (7,22,23) or proteins (24,25), as well as anomalous x-ray solution studies on proteins and nucleic acids (26,27), have revealed the specific recruitment of ions into their HSs.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4,5] Recently, there have been a great deal of theoretical and experimental studies on the ion solvation and ion effects at the electrolyte aqueous solution surfaces. [1,2,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29] Ions have long been considered to be depleted from the surface of an aqueous solution of simple electrolytes, such as the alkali halides. [30,31,32] According to the Gibbs adsorption equation, the increase of the surface tension of water with the addition of simple inorganic salts was explained by the assertion that the simple ions can only have a negative adsorption at the aqueous interface.…”
mentioning
confidence: 99%
“…As the surface has low dielectric, ions will not generally be preferred there compared with the high dielectric bulk. However, chaotropic ions with low surface charge density and/or high polarizability (such as Cl -, Br -, I -, HO 2 -and O 2 -) will favor the gas-liquid interfaces (Garrett, 2004;Jungwirth and Winter, 2008) as they only interact weakly with water but are influenced favorably by the highly polarized surface. Aqueous radicals also prefer to reside at such interfaces (Roeselová al, 2004), as do some molecular species that prefer to hydrogen bond on the outside of clathrate-like structures, like superoxide (Shi et al 2003).…”
Section: Surface Tension and Related Thermodynamicsmentioning
confidence: 99%